Management and management tools in education (Docentes 2.0 Journal, 2016)
For a teacher, he can find a way to do his job better. You should look for new teaching strategies with students who come to your classroom with unsatisfied basic needs; to take advantage of each resource to motivate its students to continue learning; turn each difficulty into a new challenge to find new solutions, to discover a new project that helps them to continue developing professionally.
Keywords: Management; management tools; education